2006
DOI: 10.1182/blood-2005-05-2103
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and apoptosis in human Philadelphia chromosome-positive lymphoblastic leukemia cell lines by treatment with the dual PPARα/γ ligand TZD18

Abstract: Treatment of adult Philadelphia chromosome-positive lymphocytic leukemia is rarely successful. We report here the effects of TZD18, a novel dual ligand specific for peroxisome proliferatoractivated receptor ␣ and ␥ (PPAR␣/␥) on Ph ؉ lymphocytic leukemia cell lines BV173, SD1, and SupB-15. Exposure of these cells to TZD18 resulted in growth inhibition in a dose-and time-dependent manner that was associated with G 1 cell cycle arrest. This effect was much stronger than that mediated by the PPAR␥ ligand pioglitaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 81 publications
1
53
0
Order By: Relevance
“…Our observations are in accordance with the previous reports that have also suggested that the antitumor activity of PPARa agonists may involve unknown pathways that are independent of blocking PPARa transcriptional activity and have been described as 'off-target' effects. 15,17,20 Cyclin D1 overexpression is a hallmark of MCL cells. It has been recently reported that inhibition of cyclin D1 in MCL cells Effects of fenofibrate on mantle cell lymphoma Z Zak et al blocks cell proliferation but is not sufficient to induce cell death in these cells.…”
Section: Minomentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations are in accordance with the previous reports that have also suggested that the antitumor activity of PPARa agonists may involve unknown pathways that are independent of blocking PPARa transcriptional activity and have been described as 'off-target' effects. 15,17,20 Cyclin D1 overexpression is a hallmark of MCL cells. It has been recently reported that inhibition of cyclin D1 in MCL cells Effects of fenofibrate on mantle cell lymphoma Z Zak et al blocks cell proliferation but is not sufficient to induce cell death in these cells.…”
Section: Minomentioning
confidence: 99%
“…Furthermore, it is well documented that activation of mouse and human PPARa often results in opposite physiological effects in the liver. 12,14 In humans, PPARa-specific agonists have been recently reported to have antitumor effects in a number of various cancer types such as acute myeloid leukemia, [15][16] chronic lymphocytic leukemia 17 and malignant tumors of the ovary, 18 liver, 19 skin, breast and lung. 20 Recently, fenofibrate was found to be the most potent drug among all of the fibrates in inhibiting the growth of various cell lines derived from melanoma, lung carcinoma, glioblastoma and fibrosarcoma in a xenograft mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed as described previously. 38 Antibodies against p-AKT (S473), p-AKT (T308) and AKT were from Cell Signaling Technology (New England Biolabs, Frankfurt am Main, Germany); antibody against ß-Actin was from Santa Cruz Biotechnology (Heidelberg, Germany).…”
Section: Measurement Of Chemokines With Elisamentioning
confidence: 99%
“…One is the extrinsic pathway that is triggered by ligation of cell death receptors leading to activation of Caspase 8. The other is the intrinsic pathway in which the bcl-2 superfamily and mitochondria are involved (Liu et al, 2006). In this case, decrease in the expression of antiapoptotic Bcl-2 protein or an increase in the level of proapoptotic Bax protein disrupts the mitochondrial membranes and releases proapoptotic proteins leading to activation of Caspase 9, as we have observed in cervical epithelium of RXRa mutant mice (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…As we mentioned, Bcl-2 promotes cell survival, whereas Bax promotes cell death (Adams and Cory, 1998), and it is known that the ratio of Bcl-2 to Bax determines survival or death following an apoptotic stimulus (Adams and Cory, 1998;Liu et al, 2006;Thomas et al, 1996). Thus, the increase in bax gene expression and the decrease in bcl-2 gene expression observed after RXRa ablation should dramatically increase cell death.…”
Section: Discussionmentioning
confidence: 93%